COMPARATIVE ANALYSIS BETWEEN THE AUDIO-VISUAL AIDED PROBLEM BASED LEARNING MODEL AND THE DIRECT LEARNING MODEL ON THE SCIENCE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Sukma, Inggita; Sudarti, Sudarti; Handayani, Rif’ati Dina (Nindikayla Institute, 2024)
To achieve effective learning, the role of teachers in designing, implementing, and evaluating instruction is crucial. Selecting a suitable instructional model based on students' characteristics and the learning situation can create an enjoyable, challenging, and motivating learning environment for students. The objective of this experimental research is to examine the significant difference between the effects of Problem-Based Learning with audiovisual media and direct instruction models on fifth-grade students at SDN Kalisat 1. This experimental study employed a quasi-experimental design known as the Post Test Only Control Group Design. The population of this study consisted of 60 fifth-grade students from SDN Kalisat 1. The selection of the experimental and control groups was done randomly, with Class VA comprising 30 students selected as the control group, while Class VB comprising 30 students selected as the experimental group. Based on the research conducted in Class V at SDN Kalisat 1, there were significant differences in the learning outcomes between the application of Problem-Based Learning with audiovisual media and direct instruction models in the subject of Natural Sciences (IPA). This can be seen from the average learning outcomes of students using Problem-Based Learning with audiovisual media, which were 77.33 with a standard deviation of 8.27, while the average learning outcomes of students using direct instruction were 72.66 with a standard deviation of 7.738. Furthermore, the t-test with a significance level of α= 0.05 and a t-table value of 2.00172 indicated that the calculated t-value (2.256) was greater than the t-table value (2.00172) and the significance value was 0.557.